Large-scale real-world data on a multidisciplinary approach to spinal cord stimulation for persistent spinal pain syndromes: first evaluation of the Neuro-Pain® nationwide screening and follow-up interactive register - Bernaerts, Lisa; Roelant, Ella; Lecomte, Frederic; Moens, Maarten; Van Buyten, Jean-Pierre; Billet, Bart; Bryon, Bart; Puylaert, Martine; Turgay, Tuna; Malone, Maureen; Theys, Tom; Van Zundert, Jan; et al. (Frontiers in Neuroscience, 2024)
SSpinal cord stimulation is a common treatment option for neuropathic pain conditions. Despite its extensive use and multiple technological evolutions, long term efficacy of spinal cord stimulation is debated. Most studies on spinal cord stimulation include a rather limited number of patients and/or follow-ups over a limited period. Therefore, there is an urgent need for real-world, long-term data. In 2018, the Belgian government initiated a nationwide secure platform for the follow-up of all new and existing spinal cord stimulation therapies. This is a unique approach used worldwide. Four years after the start of centralized recording, the first global extraction of data was performed. Herein, we present the findings, detailing the different steps in the centralized procedure, as well as the observed patient and treatment characteristics. Furthermore, we identified dropouts during the screening process, the reasons behind discontinuation, and the evolution of key indicators during the trial period. In addition, we obtained the first insights into the evolution of the clinical impact of permanent implants on the overall functioning and quality of life of patients in the long-term. Although these findings are the results of the first data extraction, some interesting conclusions can be drawn. The long-term outcomes of neuromodulation are complex and subject to many variables. Future data extraction will allow us to identify these confounding factors and the early predictors of success. In addition, we will propose further optimization of the current process.